Psychological and Pedagogical Technologies of Working with Teenagers to Level the Manifestations of Learned Helplessness - Shalaginova K.S.; Dekina E.V.; Kulikova T.I. (Психолого-педагогические исследования, 2020)
The article discusses the prerequisites for the emergence of learned helplessness in adolescents, offers psychological and pedagogical technologies for its study and prevention. Diagnostic and preventive programs are based on the selected components of learned helplessness: motivational, cognitive, and emotional. The article presents the materials of an empirical study obtained on a sample of teenagers in grades 5-6 in the number of 66 students who had a state of learned helplessness. The criteria and indicators for assigning children to a risk group based on the state of learned helplessness were marker words in the speech of a schoolchild. We used the author's questionnaire, the questionnaire “Motivation for success and fear of failure” by A.A. Rean, “Method of research of self-esteem and the level of claims” by Dembo-Rubinstein, the projective test “Nonexistent animal”, “Phillips school anxiety Test”, “Maddy's resilience Test” (adaptation by D.A. Leontiev), “Torrence creativity Test”. The study revealed the characteristics of adolescents with the phenomenon of “learned helplessness”. To overcome the conditions of learned helplessness in this category of students, the “Path to Success” program was developed and tested, recommendations were made to teachers on leveling the manifestations of learned helplessness in adolescents. To prevent and overcome the syndrome of learned helplessness, create emotional well-being of adolescents as targets of psychological influence, the formation of adequate self-esteem and the level of claims of adolescents, the development of an objective, adequate attitude to the results of their activities, orientation not to error, but to obtain new knowledge are identified.